(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This Article is focused on prevalence and religious concept of adultery in India as well as in other countries all over the world wherein we come to know that it existed from a very long time in our society but it was criticized everywhere. Even it was criticized in all religions which can be easily seen in respective religious books. The methodology used in the present Article is mixture of primary as well as secondary research. For understanding this Article, the author has included meaning, definition and legal constructs of adultery its available defences punishments all over the world problems arising out of adultery adultery issues in all religious books and religions historical background and advancement of adultery laws all over the world and its consequences. After finding out all the above-mentioned things, it was concluded by the author that adultery developed along with development of the society. Since it is not a new act and can be easily found in history of mankind, that’s why this act was always criticized. Moreover, codified laws were not there in ancient time and everyone was bound by his her concerning religion, so all religious books forbid for this act. Even after having codified laws, adultery was and has been forbidden everywhere and many countries declared it a crime.